Idealisasi Nilai Pendidikan Lingkungan dalam Novel Anak Rantau (Kajian Ekokritik) - Syarif, Nova Agusryana; Tang, Muhammad Rapi; Usman, Usman (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aimed to examined the value of environmental education in the novel Anak Rantau by Ahmad Fuadi. This research used descriptive qualitative method. Data collection method used the documentary method using reading and note-taking technique. Data analysis was carried out through several stages, namely data reduction, data presentation, and drawing conclusions. The result of this study indicated that novel Anak Rantau by Ahmad Fuadi contained the value of environmental education, namely establishing a harmonious relationship between humans and nature by maintaining and caring for nature as well as possible. So that human wisdom and prudence will be created in responding to all natural wealth with everything in it for the sake of human survival in the future.